A simple and efficient synthesis of isoindolinone derivatives based on reaction of ortho-lithiated aromatic imines with CO. Issue 40 (7th October 2015) - Li, Hai-Jun; Zhang, Yu-Qing; Tang, Liang-Fu
Abstract: A simple and efficient one-pot synthesis of 2, 3-disubstituted isoindolinones via the reaction of o -lithiated aromatic imines with carbon monoxide under one atmospheric pressure has been developed. Preliminary in vitro tests for fungicidal activity of these isoindolinone derivatives have been carried out, indicating that most of them exhibit good fungicidal activities. Graphical abstract: